2018
DOI: 10.20944/preprints201808.0295.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Review of Biomedical Applications of Contactless Imaging of Neonates using Infrared Thermography and Beyond

Abstract: The monitoring of sick newborns is a challenging task that health care providers in Neonatal Intensive Care Units (NICU) must contend with each day. Conventionally, newborns are monitored via probes that are affixed to their skin and attached to processing monitors (Fig.1). However, an alternative exists in contactless imaging to record such physiological signals (Physio-Markers), surface changes and internal structures which can be used independently of, or in conjunction with conventional monitors. Advantage… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…All these data indicate that IRI, including endothelial cell damage and extravascular fluid leakage, occurred in nonsuitable cases at the earliest timing of EVLP, and subsequently, this poor perfusion resulted in significantly lower lung surface temperatures. This is consistent with the common mechanism of thermography as noted in previous reports: poor circulation leads to lower thermography temperatures 10–14 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All these data indicate that IRI, including endothelial cell damage and extravascular fluid leakage, occurred in nonsuitable cases at the earliest timing of EVLP, and subsequently, this poor perfusion resulted in significantly lower lung surface temperatures. This is consistent with the common mechanism of thermography as noted in previous reports: poor circulation leads to lower thermography temperatures 10–14 …”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the common mechanism of thermography as noted in previous reports: poor circulation leads to lower thermography temperatures. [10][11][12][13][14] There have been several reports on thermography for the assessment of organs. Gorbach et al reported that a longer rewarming time is correlated with longer cold ischemic time and worse renal function in intraoperative assessments using thermography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that there are a range of possible sites and formulas for the measurement of proximal T and, to a lesser extent, distal T. Logically, it could be assumed that proximal T may be most accurately assessed as the average of multiple measures, from all over the proximal regions. That is, the more numerous the measurements, the more accurate the calculation of average proximal T. Indeed, some studies have calculated skin T from averages over 65 locations for a “full-body thermography” ( 59 ) or with skin infra-red thermography ( 60 ). Conversely, the use of multiple sites is at odds with practical considerations.…”
Section: Introductionmentioning
confidence: 99%